Genetic Merit of Parents and Heterosis in Cassava (Manihot esculenta Crantz) - Vanderlei da Silva Santos; Helcio Duarte Pereira; Juraci Souza Sampaio Filho; Luciano Rogério Braatz de Andrade (Horticulturae, 2025)
Cassava breeders are led to discard plants before evaluating families, failing to obtain important information, such as the genetic merit of the parents. In this work, we evaluated a Clonal Evaluation Trial (CET) with 1886 clones from 57 crosses in an augmented block design with the 15 parents used as check treatments. We applied a mixed-model framework incorporating pedigree information. Three traits (fresh root yield (FRY), dry matter content (DMC) and dry matter yield (DMY)) were evaluated, and genetic gains considering several selection intensities were investigated. Disregarding the family structure, the gains for FRY (19.96 to 30.80%) and DMY (16.63 to 27.56%) were much higher than the estimated for DMC (7.79 to 11.46%). The means of clones were very near to the mean of parents for all traits, suggesting the absence of heterosis. However, considering the data by family, heterosis varied from −4.38 to 7.53% for FRY, from −2.74 to 1.89% for DMC and from −4.36 to 6.89% for DMY. Heterosis for FRY is not negligible, although it is small. The analysis by family enables us to infer the genetic control of the traits under study. This is not possible when the family structure is disregarded.